Stochastic finite integration technique for magnetostatic problems. (16th November 2016) - Codecasa, Lorenzo; Di Rienzo, Luca
Abstract: Both nonintrusive and intrusive stochastic approaches on the basis of polynomial chaos expansion are presented for the finite integration technique over generic polyhedral grids for 3D magnetostatic linear problems. Such algorithms outperform Monte Carlo methods (when the number of random parameters is small), both in accuracy and efficiency. A novel algorithm for the intrusive approach is also provided, by which the intrusive approach becomes less computationally expensive than the nonintrusive approach. Validation is performed by solving a magnetic circuit where the reluctivity is uncertain.